2013
DOI: 10.11152/mu.2013.2066.151.df1uec2
|View full text |Cite
|
Sign up to set email alerts
|

The utility of elastography and CEUS for the differentiation between benign and malignant cervical lymphadenopaty. Three cases report

Abstract: The differentiation between benign and malignant cervical lymph nodes is a frequent challenge for the clinician. We present the cases of three patients with cervical lymphadenopaty (inflammatory lymph node, lymphoma, and metastasis of laryngeal carcinoma) in which the use of elastography and contrast enhanced ultrasonography had substantial contribution to the correct final diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
1
6
0
1
Order By: Relevance
“…These cases show that, in spite of progress in the assessment of neck lymph nodes with US and the use of new techniques such as elastography, it is still risky to formulate a diagnosis of histopathological value, based solely on the US appearance. Further developments such as contrast enhanced ultrasonography might increase the diagnosis accuracy [4,18]. The clue to an accurate diagnosis relies in the corroboration of clinical data with US and other imaging information, having in mind that confrontation with pathology is always necessary.…”
Section: Discussionmentioning
confidence: 99%
“…These cases show that, in spite of progress in the assessment of neck lymph nodes with US and the use of new techniques such as elastography, it is still risky to formulate a diagnosis of histopathological value, based solely on the US appearance. Further developments such as contrast enhanced ultrasonography might increase the diagnosis accuracy [4,18]. The clue to an accurate diagnosis relies in the corroboration of clinical data with US and other imaging information, having in mind that confrontation with pathology is always necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Because many diseases correlate with changes in the mechanical properties of tissues, this technique has been successfully applied in detecting and assessing various pathologies of thyroid gland, breast, lymph nodes, major salivary gland, prostate, kidney, and liver [1][2][3][11][12][13][14][15][16][17]. However, to our knowledge, no study has been reported previously in the medical literature using real time sonoelastography to assess gallbladder polyps.…”
Section: Discussionmentioning
confidence: 52%
“…Newer sonographic techniques such as contrast enhanced US (CEUS) gave promising results on differentiating benign and malignant gallbladder lesions [21]. But administration of contrast agent, detection of the contrast enhancement pattern or wash-out phenomenon of the contrast agent, the need for perfusion quantification parameters, and application of transducer in a stable position for at least 3 minutes may limit the use of CEUS [17,21]. We think that elastography can be useful in the characterization of gallbladder polyps as a new technique, although there is insufficient data at present for this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Гомогенное контрастирование лимфатических узлов при КУУЗИ характерно как для лимфом, так и для реактивных лимфатических узлов [22,23]. По данным мировой литературы, разные виды лимфом с поражением периферических лимфатических узлов при КУУЗИ имеют различное контрастирование: для В-клеточной лимфомы характерен центральный тип васкуляризации и незначительное контрастирование, а для Т-клеточной лимфомы характерна васкуляризация по периферии и интенсивное гомогенное контрастирование [24,25]. В нашем исследовании при ультразвуковом контрастировании лимфатического узла с лимфопролиферативными изменениями также было выявлено диффузное гомогенное контрастирование как из периферии к центру узла, так и наоборотот центру к периферии, что свидетельствует о наличии многочисленных измененных сосудов.…”
Section: обсуждение и выводыunclassified